PENGARUH MEDIA SOSIAL DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MAHASISWA BARU KULIAH DI UM PALOPO - Asmadi, Indra; M. Anwar, Suhardi; Duriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of social media and service quality on new students' decisions in choosing Muhammadiyah University of Palopo. By adopting a quantitative approach, this study involved 100 new student respondents who were taken through a simple random sampling technique. Data was collected using a questionnaire with a Likert scale consisting of 28 questions. The results of the analysis show that social media has a significant influence on new student decisions with a calculated T value of 6.999, which is greater than the T table of 1.984, as well as a significance value of 0.001 which is smaller than the 0.05 significance limit. This indicates that information obtained from social media, such as promotions and testimonials, is able to influence prospective students' perceptions of universities. Furthermore, service quality also shows a significant influence on new student decisions, with a calculated T value of 6.616 and a significance value of 0.001, which indicates that good academic and administrative services contribute to the level of satisfaction of prospective students in choosing a university. In addition, multiple linear regression analysis shows that social media and service quality simultaneously have a significant influence on new student decisions, indicated by a calculated F value of 344.948, which is greater than the F table of 3.939, and a significance value of 0.001. These findings confirm the importance of using social media and improving service quality as effective strategies in attracting prospective students. Thus, this study provides valuable insights for Universitas Muhammadiyah Palopo to formulate more appropriate and attractive marketing policies for prospective new students in the future.